Pharmacometrics in pain management - Wang, Yaning; Liu, Jiang; Zhu, Hao; Ji, Ping (Henry Stewart Talks, 2015)
What is pain, Classification of pain, What is pharmacometrics, Modeling in chronic & acute pain, Pharmacometrics in clinical patient care, Drug dosing advisory displays, Pharmacometrics in opioid treatment, Case examples: fixed dose combination, Case examples: acetaminophen pediatric dosing regimen